ADAPTIVE LEADERSHIP IN HUMAN RESOURCE MANAGEMENT FOR MSME DIGITALIZATION - Iin Angraen Napu; Darman; Ismiyati A Noe (Jurnal Ilmu Manajemen dan Bisnis, 2025)
The phenomenon of digital transformation has significantly reshaped the operational landscape of Micro, Small, and Medium Enterprises (MSMEs) in Indonesia. However, many MSMEs have struggled to adopt digital technology effectively due to limitations in human resources and weak leadership during change management. This study aims to explore the role of adaptive leadership in managing human resources during the digitalization of MSMEs using a qualitative approach based on a narrative review. Data were synthesized from relevant national and international literature published within the last five years. The findings reveal that adaptive leadership plays a critical role in creating a flexible work environment, fostering organizational learning, and reducing resistance to digital change. Adaptive leaders not only formulate strategies but also promote human capital development through participatory training and cultural transformation. These insights emphasize that the success of MSME digitalization depends not only on technological readiness but also on leadership quality capable of navigating uncertainty with a reflective and collaborative approach. This study contributes conceptually to leadership theory development within the digital MSME context and offers a basis for designing MSME empowerment policies rooted in leadership capacity building.